2022
DOI: 10.1001/jamanetworkopen.2022.26182
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Head Trauma in Infants During the COVID-19 Pandemic in the Paris Metropolitan Area

Abstract: IMPORTANCEThe COVID-19 pandemic and the containment and mitigation measures taken were feared to be associated with increased child abuse. OBJECTIVE To investigate the trend of abusive head trauma (AHT) incidence and severity in infants during the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTSIn a time-series analysis of a longitudinal, populationbased, cohort study, all consecutive cases of AHT in infants younger than 12 months old referred between January 2017 and December 2021 to Necker Hospital for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Our multicentric data across different national territories had the advantage of representing a wide population and were complementary to previous studies on this subject. Indeed, the results were in agreement with those described in the Capital Metropolitan Area ( Lãzãrescu et al, 2022 ), with a similar increase rate (almost twice) in the incidence of AHT during the COVID-19 pandemic. We could think that the lockdown and curfews during COVID-19 pandemic would not have had similar consequences in taking care of children, due to different geographic living conditions and the variety of ways of life and promiscuity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our multicentric data across different national territories had the advantage of representing a wide population and were complementary to previous studies on this subject. Indeed, the results were in agreement with those described in the Capital Metropolitan Area ( Lãzãrescu et al, 2022 ), with a similar increase rate (almost twice) in the incidence of AHT during the COVID-19 pandemic. We could think that the lockdown and curfews during COVID-19 pandemic would not have had similar consequences in taking care of children, due to different geographic living conditions and the variety of ways of life and promiscuity.…”
Section: Discussionsupporting
confidence: 90%
“…However, in France, no significant increase in children with subdural hematoma was observed during the first year of the pandemic compared with the two previous years ( Caron et al, 2022 ). But an important increase of the incidence and the severity of AHT was observed in the single regional pediatric neurosurgery center in Paris during the first two years of the pandemic ( Lãzãrescu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in AHT in Paris in 2021 may of course be an isolated finding by Lãzãrescu et al 1 2) why did the factors that worked in 2020 start to fail? By determining which policies or factors may have helped delay the expected child maltreatment surge, we might prevent future harm to children.…”
Section: + Related Articlementioning
confidence: 98%
“…Because its incidence is known to increase when families experience stressors and financial strain, it has been the focus of several studies to date on the COVID-19 pandemic. In their new study, Lãzãrescu et al examined whether the pandemic was associated with any changes in AHT incidence in metropolitan Paris. Focusing on infants younger than 12 months seen for subdural hemorrhage from AHT at the regional pediatric neurosurgery center, they conducted a population-based, time-series cohort study.…”
mentioning
confidence: 99%
“…It remains a common problem with an incidence estimated at 15-30/100000 children < 1 year and an overall mortality rate of 15-38% and long-term neurologic deficits in up to 80% of surviving victims, thus associated with significantly worse outcomes compared to accidental traumatic brain injury [4][5][6][7]. Furthermore, a recent study has shown a marked increase in AHI incidence and severity during the COVID-19 pandemic, stressing the need for clinical awareness and prevention measures [8]. As a survey among members of the International Society for Pediatric Surgery (ISPN) has shown, this condition is associated with unique challenges and intervention opportunities for neurosurgeons [9].…”
Section: Introductionmentioning
confidence: 99%